2006
DOI: 10.4141/p06-002
|View full text |Cite
|
Sign up to set email alerts
|

A genetic examination of early flowering and maturity in Canadian spring wheat

Abstract: A genetic examination of early flowering and maturity in Canadian spring wheat. Can. J. Plant Sci. 86: 995-1004. Under short-season western Canadian growing conditions, vernalization non-responsiveness is generally considered a preferable spring wheat (Triticum aestivum L.) phenotype, to avoid inconsistent maturity and yield patterns. The objectives of this study were to investigate the genetic factors affecting early flowering and maturity, and related agronomic traits, in a set of five Canadian spring wheat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…The same result was reported in other works on wheat (Khalifa, 1998;Zhang et al, 1985;Iqbal et al, 2006;Bhatia et al, 1979;Sing & Paroda, 1986). For GFD under both locations and PH at Zarghan, the Baker ratio indicated the importance of non-additive gene effects.…”
Section: Baker Ratiosupporting
confidence: 79%
See 1 more Smart Citation
“…The same result was reported in other works on wheat (Khalifa, 1998;Zhang et al, 1985;Iqbal et al, 2006;Bhatia et al, 1979;Sing & Paroda, 1986). For GFD under both locations and PH at Zarghan, the Baker ratio indicated the importance of non-additive gene effects.…”
Section: Baker Ratiosupporting
confidence: 79%
“…Selection for early flowering under non-vernalized conditions may aid in the breeding of vernalization non-responsive or early-matured spring cultivars (Iqbal et al, 2006). Photoperiod responsive genes play a key role in heading time under field conditions in the cultivars that have already been vernalized (Snape et al, 2001).…”
mentioning
confidence: 99%
“…Early-maturing wheat has been correlated with increased yield in competitive organic farming systems (Mason et al 2007b) and early heading associated with competitive ability (Huel and Hucl 1996). Flowering in wheat is influenced by photoperiod, vernalization, and earliness per se genes (Iqbal et al 2006). Cousens et al (2003a) reported reduced time to flower did not increase competitive ability.…”
Section: Discussionmentioning
confidence: 99%
“…Winter wheat requires exposure to a continuous cold treatment (vernalization) prior to reproductive initiation. Spring wheat generally does not have such a requirement, but some cultivars do respond to cold by flowering early (Levy and Peterson 1972;Jedel et al 1986;Iqbal et al 2006). Vernalization sensitivity/insensitivity in hexaploid wheat is controlled by alleles at the major vernalization loci, Vrn-A1, Vrn-B1, Vrn-D1 and Vrn-D5 (Pugsley 1972).…”
mentioning
confidence: 98%